(untitled) (Journal of Computational Mathematics, 2000)
The dimension of the bivariate spline space S^r_n0394 may depend on geometric properties of triangulation 0394, in particular if n is not much bigger than r. In the paper, the blossom approach to the dimension count is outlined. It leads to the symbolic algorithm that gives the answer whether a triangulation is singular or not. The approach is demonstrated on the case of Morgan-Scott partition and twice differentiable splines. 00a0